2012
DOI: 10.4236/ajcc.2012.14016
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Capacity for Resilience among Coastal Counties of the U. S. Northern Gulf of Mexico Region

Abstract: Many have voiced concern about the long-term survival of coastal communities in the face of increasingly intense storms and sea level rise. In this study we select indicators of key theoretical concepts from the social-ecological resilience literature, aggregate those indicators into a resilience-capacity index, and calculate an index score for each of the 52 coastal counties of Louisiana, Texas, Mississippi, Alabama and Florida. Building upon Cutter’s Social Vulnerability Index work [1], we use Factor Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…The results show that health service, sex ratio, ratio of urban to rural, access to open space, road density and slope condition are statistically significant in characterizing disaster resilience. The six variables validated in this study are consistent with the set of variables mentioned as proxy for community resilience to other natural hazards [8,13,16,61]. This implies that, in general, investment in promoting adaptation activities and policies for one kind of natural hazard should have a synergistically positive effect on community resilience to other natural hazards; and to flash flood hazards, especially in regions within China, the six variables play more dominant roles in determining the recovery capability that was represented by the return speed of people's living and industrial productivity.…”
Section: Conclusion and Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The results show that health service, sex ratio, ratio of urban to rural, access to open space, road density and slope condition are statistically significant in characterizing disaster resilience. The six variables validated in this study are consistent with the set of variables mentioned as proxy for community resilience to other natural hazards [8,13,16,61]. This implies that, in general, investment in promoting adaptation activities and policies for one kind of natural hazard should have a synergistically positive effect on community resilience to other natural hazards; and to flash flood hazards, especially in regions within China, the six variables play more dominant roles in determining the recovery capability that was represented by the return speed of people's living and industrial productivity.…”
Section: Conclusion and Discussionmentioning
confidence: 63%
“…Previous literature had found that a larger amount of urban green areas can improve the ecological condition [15], while lower river density and a flatter surface reduce the risk of storm surge inundation and secondary landslides [12]. Lower elevation and slope also provide an improvement of the accessibility and ease of rescue work [13,58]. Note: * Statistic unit: per sub-district (or town); The demographic data was derived from the published 2010 Population Census of China (PCC); The GDP data was obtained from a 1 km grid GDP data of China (2010) (Global Change Research Data Publishing and Repository, 2014) (GCRD); Information Points were downloaded from the Open Street Map (OSM); Build-up Area was derived from the artificial land cover in GLOBELAND30 dataset [50]; DEM and slope data were derived from the ASTER GDEM dataset published in 2009.…”
Section: Connecting the Measurements Of Recovery To Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Previous assessments of the County's adaptive capacity are: Cutter et al [17], Reams et al [18], NOAA's Human Dimensions [19], and SHELDUS™ [20]. Cutter et al [17] collected six resilience parameters: ecological, social, economic, infrastructure, institutional capacity, and community competence.…”
Section: Introductionmentioning
confidence: 99%
“…A later version of the method showed Jefferson County having a medium SoVI, where principal component analysis was used to point to the main components/indicators that account for the greatest variance within the dataset [21]. Reams et al [18] followed the methodology of Cutter et al [17] but with applied the method to fifty two coastal counties of the US northern Gulf of Mexico region using forty three indicators to measure community resilience represented by demographics, social capital, economic resources, local government actions, and environmental aspects. Principal component analysis was performed to derive eleven components that accounted for 76.4% of variance of all the indicators.…”
Section: Introductionmentioning
confidence: 99%